2007
DOI: 10.1103/physrevb.75.035115
|View full text |Cite
|
Sign up to set email alerts
|

First-principlesLDA+UandGGA+Ustudy of cerium oxides: Dependence on the effective U parameter

Abstract: The electronic structure and properties of cerium oxides ͑CeO 2 and Ce 2 O 3 ͒ have been studied in the framework of the LDA+ U and GGA͑PW91͒ + U implementations of density functional theory. The dependence of selected observables of these materials on the effective U parameter has been investigated in detail. The examined properties include lattice constants, bulk moduli, density of states, and formation energies of CeO 2 and Ce 2 O 3 . For CeO 2 , the LDA+ U results are in better agreement with experiment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(138 citation statements)
references
References 53 publications
14
120
2
Order By: Relevance
“…In this study, we used the GGA (generalized gradient approximation) functional PBE developed by Perdew et al 46 The DFT+U (LDA+U and GGA+U) methods have been shown to overcome the inability of LDA and GGA to describe the localized Ce4f electrons in ceria with reduced cerium ions. 21,22 The choice of the U parameter value was explored in several previous studies 21,[47][48][49][50] and it has been noted (Ref. 50 and elsewhere) that LDA+U actually provides a better overall description of ceria than GGA+U.…”
Section: Methods a Computational Detailsmentioning
confidence: 99%
“…In this study, we used the GGA (generalized gradient approximation) functional PBE developed by Perdew et al 46 The DFT+U (LDA+U and GGA+U) methods have been shown to overcome the inability of LDA and GGA to describe the localized Ce4f electrons in ceria with reduced cerium ions. 21,22 The choice of the U parameter value was explored in several previous studies 21,[47][48][49][50] and it has been noted (Ref. 50 and elsewhere) that LDA+U actually provides a better overall description of ceria than GGA+U.…”
Section: Methods a Computational Detailsmentioning
confidence: 99%
“…Obviously, in order to optimize the engineering applications of the NPs, one must have a complete understanding of the atomic scale processes responsible for the properties of the NPs. Consequently, there have been a number of atomistic computer simulations of the ceria NPs [10][11][12], in addition to, of course, the considerable body of literature on the modelling of point defect properties, including electronic structure of the bulk structure and surfaces [13][14][15]. However, available computer resources have usually constrained the size of the NPs which could be modelled to those somewhat smaller than even the 2 nm range.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty to correctly model the electronic structure of Ce 2 O 3 with GGA had already been pointed out by Skorodumova et al 54 One proposed solution has been to apply a Hubbard U on the cerium f-electrons. 55 While fitting a U value for Ce is beyond the scope of this work, we indeed observe the reaction energy getting closer to the experimental data by applying a moderate U value (U = 3 eV) on the f electrons in Ce for both CeCrO 3 and CeAlO 3 (see Table I). The other f-containing elements (i.e., U and La) do not show as large discrepancies as Ce (with the exception of one uranium based compound Cs 2 UO 4 ).…”
mentioning
confidence: 96%